Case Series : Operative vs Non-Operative Management in Grade III Pancreatic Injury - Irawan, Andry; Clinton, Clinton; D, Sutanto; F, Agustina (Medicinus, 2019)
Introduction: Pancreatic injury is a rare case, caused by blunt or sharp trauma. Difficulty in making diagnose on pancreatic trauma cases are associated with high mortality, and the treatment can be either operative or conservatively. However, It is still unclear which treatment is more favorable.Case: We present 2 cases of Grade III pancreatic injury with stable hemodynamic who suffered bicycle accident. First case, 12-year-old boy complaining severe pain on the upper left abdomen (VAS 9-10) and get worsening by time, with vomiting. The patient underwent distal Pancreatectomy-Splenectomy. Second case, 8-year-old boy complaining of pain on the upper left abdomen (VAS 6-7) without extension on whole abdominal region with vomiting and fever. The patient was treated conservatively. In both cases, patient was discharged with improvement. However, about 3 months later patients who were treated conservatively developed into a pseudocyst.Conclusion: The selection of management in grade III pancreatic injury can be operative or conservative depending on clinical findings such as hemodynamic condition and the quality of abdominal pain. But the occurrence of pseudocysts pancreas is another surgical challenge.